Assessing the reliability of CBCT-based AI-generated STL files in diagnosing osseous changes of the mandibular condyle: a comparative study with ground truth diagnosis - KESER, GAYE; NAMDAR PEKİNER, FİLİZ MEDİHA (My University, 2023)
Objectives: This study aims to evaluate the reliability of AI-generated STL files in diagnosing osseous changes of the mandibular condyle and compare them to a ground truth (GT) diagnosis made by six radiologists. Methods: A total of 432 retrospective CBCT images from four universities were evaluated by six dentomaxillofacial radiologists who identified osseous changes such as flattening, erosion, osteophyte formation, bifid condyle formation, and osteosclerosis. All images were evaluated by each radiologist blindly and recorded on a spreadsheet. All evaluations were compared and for the disagreements, a consensus meeting was held online to create a uniform GT diagnosis spreadsheet. A web-based dental AI software was used to generate STL files of the CBCT images, which were then evaluated by two dentomaxillofacial radiologists. The new observer, GT, was compared to this new STL file evaluation, and the interclass correlation (ICC) value was calculated for each pathology. Results: Out of the 864 condyles assessed, the ground truth diagnosis identified 372 cases of flattening, 185 cases of erosion, 70 cases of osteophyte formation, 117 cases of osteosclerosis, and 15 cases of bifid condyle formation. The ICC values for flattening, erosion, osteophyte formation, osteosclerosis, and bifid condyle formation were 1.000, 0.782, 1.000, 0.000, and 1.000, respectively, when comparing diagnoses made using STL files with the ground truth. Conclusions: AI-generated STL files are reliable in diagnosing bifid condyle formation, osteophyte formation, and flattening of the condyle. However, the diagnosis of osteosclerosis using AI-generated STL files is not reliable, and the accuracy of diagnosis is affected by the erosion grade.
Keywords: Diş Hekimliği; Klinik Bilimler; Oral Diagnoz ve Radyoloji; Bilgisayar Bilimleri; Algoritmalar; Yapay Zeka, Bilgisayarda Öğrenme ve Örüntü Tanıma; Sağlık Bilimleri; Mühendislik ve Teknoloji; Dentistry; Clinical Sciences; Oral Diagnosis and Radiology; Computer Sciences; algorithms; Artificial Intelligence, Computer Learning and Pattern Recognition; Health Sciences; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Klinik Tıp; Bilgisayar Bilimi; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; Clinical Medicine (MED); Engineering, Computing & Technology (ENG); CLINICAL MEDICINE; COMPUTER SCIENCE; DENTISTRY, ORAL SURGERY & MEDICINE; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Bilgisayarla Görme ve Örüntü Tanıma; Bilgisayar Bilimi Uygulamaları; Yapay Zeka; Bilgisayar Bilimi (çeşitli); Genel Bilgisayar Bilimi; Fizik Bilimleri; Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Computer Vision and Pattern Recognition; Computer Science Applications; Artificial Intelligence; Computer Science (miscellaneous); General Computer Science; Physical Sciences; temporomandibular joint; mandibular condyle; stereolithography; cone-beam computed tomography; artificial intelligence